Nusa Penida: Land Use, Tourism, and Sustainability - Fithor, Alin; Nugroho, Beni Sabdo; Prihadi, Donny Juliandri; Ainni, Chusnul Firaqie; Purwanti, Frida (Indonesian Fisheries Research Journal, 2025)
Nusa Penida's coastal communities rely on its rich marine resources for livelihoods, primarily through fishing, seaweed cultivation, and tourism. This study analyzes land use changes in Jungut Batu Village, Nusa Lembongan, using secondary data and Google Earth Pro, revealing a significant shift from seaweed cultivation to tourism development between 2009 and 2020, with a temporary reversion to seaweed cultivation during the pandemic. This transformation highlights evolving economic dynamics and environmental impacts. While the shift towards ecotourism represents a potential evolution in sustainable land use, the adverse effects of mass tourism necessitate a transition to eco-friendly and sustainable practices. Effective collaboration among communities, tourism stakeholders, and government, as well as further research, is crucial to developing a genuinely sustainable ecotourism model for Nusa Penida with contribution of society has accpet for last moment.